Dopamine D1 receptor subtype mediates acute stress-induced dendritic growth in excitatory neurons of the medial prefrontal cortex and contributes to suppression of stress susceptibility in mice. Issue 8 (August 2018) - Shinohara, R; Taniguchi, M; Ehrlich, A; Yokogawa, K; Deguchi, Y; Cherasse, Y; Lazarus, M; Urade, Y; Ogawa, A; Kitaoka, S; Sawa, A; Narumiya, S; et al.
Abstract Dopamine in prefrontal cortices is implicated in cognitive and emotional functions, and the dysfunction of prefrontal dopamine has been associated with cognitive and emotional deficits in mental illnesses. These findings have led to clinical trials of dopamine-targeting drugs and brain imaging of dopamine receptors in patients with mental illnesses. Rodent studies have suggested that dopaminergic pathway projecting to the medial prefrontal cortex (mPFC) suppresses stress susceptibility. Although various types of mPFC neurons express several dopamine receptor subtypes, previous studies neither isolated a role of dopamine receptor subtype nor identified the site of its action in mPFC. Using social defeat stress (SDS) in mice, here we identified a role of dopamine D1 receptor subtype in mPFC excitatory neurons in suppressing stress susceptibility. Repeated social defeat stress (R-SDS) reduces the expression of D1 receptor subtype in mPFC of mice susceptible to R-SDS. Knockdown of D1 receptor subtype in whole neuronal populations or excitatory neurons in mPFC facilitates the induction of social avoidance by SDS. Single social defeat stress (S-SDS) induces D1 receptor-mediated extracellular signal-regulated kinase phosphorylation and c-Fos expression in mPFC neurons. Whereas R-SDS reduces dendritic lengths of mPFC layer II/III pyramidal neurons, S-SDS increases arborization and spines of apical dendrites of these neurons in a D1 receptor-dependent manner. Collectively, our findings show that D1 receptor subtype and related signaling in mPFC excitatory neurons mediate acute stress-induced dendritic growth of these neurons and contribute to suppression of stress susceptibility. Therefore, we propose that D1 receptor-mediated dendritic growth in mPFC excitatory neurons suppresses stress susceptibility.